Diseño de la maestría modular nuevas tecnologías de la Información para la educación en la plataforma moodle dela universidad de Granma. - Medina Matute, Víctor Hugo (2007)
It is carried out an evaluation historical-tendencial and psicopedagógica of the Educational Technology and the learning atmospheres, as tools that allow to elevate the excellence of the educational process, highlighting the importance from the Education to Distance to Modulate and the interactive platforms in the graduate degree. The results of this work include a critical analysis of available different platforms for the education, with the objective of selecting the most appropriate to contribute to the development of the master New Technologies of the Information for the education. The platform Moodle is used, organizing the resources and consultation materials in three Graduates, which have three Modules organized in two courses each one. The collaborative work is developed in groups and the interactividad between professors and students.